PENGARUH IKLIM SEKOLAH TERHADAP MUTU PENDIDIKAN DI SEKOLAH DASAR - Yohanes Wendelinus Dasor (JIPD (Jurnal Inovasi Pendidikan Dasar), 2022)
The purpose of this study was to describe the effect of school climate on improving the quality of education. The research method used is literature study. Based on the results of the study, it shows that the school climate has an effect on improving the quality of education. School climate refers to the work atmosphere felt by personnel based on their interactions when they relate to other personnel in the school environment. school climate as an intangible but important for an organization. School climate is analogous to the personality of an individual. By referring to the analogy of school climate with personality, the school climate is definitely different from one another. School climate is understood as a manifestation of school personality that can be evaluated on a continuum from open school to closed school climate. An open school climate is based on respect, trust and honesty, and provides opportunities for teachers, school management and students to get involved constructively and cooperatively with one another. Therefore the core of the school climate is how we treat each other. School climate as the quality and character of school life that reflects the norms, goals, values, interpersonal relationships, teaching and learning practices and organizational structure. Thus, there are ten dimensions of school climate measurement which are grouped into 4 categories that have an effect on improving the quality of education, namely: safety, teaching and learning, interpersonal relationships and institutional environment.